If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1a + -2 + 3 = -2 Reorder the terms: -2 + 3 + 1a = -2 Combine like terms: -2 + 3 = 1 1 + 1a = -2 Solving 1 + 1a = -2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 1a = -2 + -1 Combine like terms: 1 + -1 = 0 0 + 1a = -2 + -1 1a = -2 + -1 Combine like terms: -2 + -1 = -3 1a = -3 Divide each side by '1'. a = -3 Simplifying a = -3
| -112=7n | | 9=11y | | 6+-14= | | 3(y+7)-4y=2y-3(y-7)+8y | | 5t+10-9= | | 5-3x=0 | | 3(2x-5)+4=31 | | 7x+3x+5=0 | | 5x-y=8 | | 9n=-5 | | 9x-4=3x+3 | | 4(x+5)=3(x-6) | | x+11=3x+5 | | 3t-(5t-1)=9 | | x+15=4x+6 | | 6-j=14 | | x+4y=16 | | 5(a+3)=8a | | y=4x^2+1 | | x^5+2x^4-10x^3-20x^2-9x=18 | | -5.2(2y+4)-2.5(3y-6)= | | 4x^2+1=0 | | 7x+34=3x+2 | | 100[0.08(x+6)]= | | 8(x-2)=32 | | 4p-(p-5)=50 | | 4x-5=5-x | | 3x+20=x+4 | | 2x+-8=8x+5 | | 38=19t | | y^3-5y^2=0 | | 18-3x=x-6 |